Orphan Disease: Infantile Systemic Hyalinosis - Ye.V. Ponochevnaia; Ye.N. Okhotnikova; O.F. Zarudniaia; V.T. Leush; Ya.I. Doronina; Ye.I. Usova; I.V. Hedeon (Zaslavsky O.Yu., 2015)
Infantile systemic hyalinosis - one of the forms of systemic hyaline fibromatosis - is a rare, fatal progressive disease with autosomal recessive inheritance, which is characterized by the accumulation of hyaline substance in different tissues of the body, including the skin, joints, bones and internal organs. This article describes a case of infantile systemic hyalinosis in a boy aged 1 year 11 months. Phenotype characteristics: tight formation in the joints with hyperpigmentation over them, progressive joint contractures, diffuse cutaneous syndrome, osteoporosis, bone fractures, short stature, persistent diarrhea and results of histological examination of tumor fragment allow us to suspect this pathology. The final diagnosis can be confirmed by molecular genetic tests. Specific therapy for infantile systemic hyalinosis doesn't exist. Most children die before 2 years of age. Adolescents suffering from this disorder disease are mostly disabled, confined to bed because of progressive contractures.